Analysis of mathematical representation ability based on students' thinking style in solving open-ended problems - Hadiastuti, Dita Indah; Soedjoko, Edy (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aimed to know whether students’ mathematical representation ability reach the classical completeness and to describe students’ mathematical representation based on their thinking style, namely Concrete Sequential (CS), Abstract Sequential (AS), Abstract Random (AR), and Concrete Random (CR). This study used mixed methods as the research design. Population in this study was 10th graders in one vocational school in Pati. The sample was a class chosen randomly. The subjects of this research were 8 students consisted of 2 of every thinking style type. The methods of data collection of this research were questionnaires of thinking style, mathematical representation ability test, interviews, and documentation. The results showed that: (1) students’ mathematical representation ability reached the classical completeness and (2) the students’ mathematical representation ability based on their thinking style are (a) the CS students have moderate visual ability, excellent symbolic ability, and poor verbal ability; (b) the AS students have moderate visual ability, excellent symbolic ability and less verbal ability; (c) the AR students have moderate visual and verbal ability, and good symbolic ability; and (d) the CR students have moderate visual ability, excellent symbolic ability, and poor verbal ability.